Checklist of butterflies from the rupestrian grasslands of Serra do Cipó, Minas Gerais, Brazil (Lepidoptera: Papilionoidea) - A. C. V. Pires; M. V. Beirão; G. W. Fernandes; I. F. Oliveira; G. C. N. Pereira; V. D. Silva; O. H. H. Mielke; M. Duarte (SHILAP, 2018)
The aim of this study is to provide a list of the butterflies (Lepidoptera: Papilionoidea) that occur in the rupestrian grasslands of Serra do Cipó, Minas Gerais, Brazil. Butterflies were sampled using VSR traps and entomological nets in seven undisturbed plots between 800 and 1400m above sea level. We collected 1,520 individuals belonging to 172 species. Among these species, four are on the Brazilian list of endangered species: Cunizza hirlanda planasia (Stoll, 1790), Magnastigma julia Nicolay, 1977, Strymon ohausi (Spitz, 1933) and Rhetus belphegor (Westwood, 1851).